HIGH COURT HEARS TOBACCO CASE AHA, OTHERS SUBMIT BRIEF. FLIGHT ATTENDANTS SUE TOBACCO FIRMS (Tufts Archival Research Center, 2007)
Handwritten; Article in the American Heart News reporting on the brief submitted to the Supreme Court by the American Heart Association. Challenges that warning labels did not absolve the corporation of liability for smokers' illness relating to tobacco use. Adds that in the opinion of health agencies, warning labels failed to educate the consumers about the risk of smoking.